PHYTOASSEMBLY AND PHARMACOLOGICAL ACTIVITY ON MORINGA OLEIFERA: A REVIEW - MALAGE, ANIKET; JADHAV, SUPRIYA; YOGEKAR, TEJASWINI; SHARMA, SAMEER (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Moringa oleifera is a plant that has copious medicative properties and widely known as “drumstick plant” or “horseradish plant” and most widely vascular plant in India. This is a nutritional plant (herb) that consists of many pharmacological and biological exertion such as antiasthmatic, diuretic, antiepileptic, cardiovascular as well as antioxidants and also beneficial in wound healing enterprise. The anti-asthmatic action of M. oleifera seeds kernel ethanolic extract evoked by histamine and acetylcholine aerosol. Pre-treatment by ethanol gives the extract of M. oleifera also diminished carrageenan convinced rat paw edema that was comparable to standard diclofenac sodium. This review summarizes the biological exertion such as a cardiovascular, diuretic, and biological activities such as antimicrobial, antiepileptic, and anti-allergic activities and also provides pharmacological activities in essence anti-cancer, anti-diabetic, and anti-asthmatic activities.